INOVAÇÃO TECNOLÓGICA NO IFPR CAPANEMA: DA PROSPECÇÃO A INOVAÇÃO - Schmitt, Marcos Fernando (2019)
One of the major problems, or challenge, of higher education institutions (HEIs), including Federal Institutes, especially in regions far from capitals and large centers, is to try to interact the local productive sector with research, extension and innovation linked to the educational system of this HEI, which could lead to innovations in processes, products and equipment that would economically leverage the sector. The main goal of this work was to promote a series of technological extensionist events, where the productive sector could bring the demand to the researchers, besides requesting other types of innovations. The techniques used to develop the work were: planning the actions, specially observing and choosing the strategic area of each event, as well as the definition of the dates and places where the events would take place; which productive sectors would be invited, besides the students and teachers involved; and last but not least, the strategic planning of the events themselves, with the definition, mainly, on the schedule and the duration of the events. During the events, records of the demands were created, which company or producer requested, who are the interested ones and who could help with the development of the innovative solution or, maybe, application of existing solutions. Once the process and / or the product to be developed was chosen, researches were made about the state of knowledge of the subject and verified whether the requested demand and the process to be developed were an inventive act or not.